A CASE STUDY: OBSTRUCTIONS ENCUMBERING THE TEACHER’S INCORPORATION OF ICT IN ENGLISH CLASSROOMS - Aziz, AzureenbintiAbd; Shah, ParilahbintiMd (International Journal of Research -GRANTHAALAYAH, 2015)
The government has declared that all Malaysians that no one; both in rural and urban areas; would be divested from the Information and Communication Technology (ICT) development. This calls for a need for teachers nationwide to make essential adjustments to the teaching and learning process. This paper takes a closer gaze on the obstructions faced by teachers in integrating ICT tools in teaching English language in the classrooms. This study aspires at determining why the teachers do not use ICT in the classrooms even they were utterly encouraged by sufficient technical supports.10 English teachers from a Secondary School were interviewed and their views and thoughts were discussed. The findings exposed that even the school is highly resourced with ICT tools and facilities, obstructions such as lack of time, amount of workload, lack of ICT skills and teachers’ negative attitudes towards ICT were hindering the teachers to incorporate ICT in their teaching. However, the teachers should be competent to shape and systematize their learning environment in non-traditional ways by merging the ICT with new pedagogy.